2021
DOI: 10.18280/ijsse.110206
|View full text |Cite
|
Sign up to set email alerts
|

How Far Disaster Management Implemented Toward Flood Preparedness: A Lesson Learn from Youth Participation Assessment in Indonesia

Abstract: Flood is a common and frequent natural disaster in many countries that causes huge economic losses and casualties every year. Youth participation in flood disaster management (FDM) has not been much explored, especially in the non-prone area but contributing to flooding resilience. Therefore, this study aims to identify youth participation in disaster management to help an improvement in preparedness action. The research was conducted using a qualitative model: case study research, involving 191 young people a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Based on the rules of spatial planning implementation article 195 paragraph 1, control of spatial utilization is the duty and authority of the provincial and regency / city governments [36]. Planning directions in several areas in the Walanae watershed based on the results of field observations and data analysis of land cover and spatial patterns that can be actualized include, in the settlement area, directions should be carried out by making two-story houses, normalizing drainage around the Walanae watershed, especially cleaning water hyacinth, counseling related to flood mitigation, increasing the scale of cooperation and communication between the government and the community, and establishing and improving the Flood Early Warning System (FEWS) [37,38]. In agricultural areas, the direction is to limit agricultural activities within a minimum radius of 100 meters from the river border, clean drainage, build embankments, implement the concept of Soil and Water Conservation, apply agroforestry patterns, and build retention ponds or infiltration wells [39].…”
Section: Flood Mitigation Strategymentioning
confidence: 99%
“…Based on the rules of spatial planning implementation article 195 paragraph 1, control of spatial utilization is the duty and authority of the provincial and regency / city governments [36]. Planning directions in several areas in the Walanae watershed based on the results of field observations and data analysis of land cover and spatial patterns that can be actualized include, in the settlement area, directions should be carried out by making two-story houses, normalizing drainage around the Walanae watershed, especially cleaning water hyacinth, counseling related to flood mitigation, increasing the scale of cooperation and communication between the government and the community, and establishing and improving the Flood Early Warning System (FEWS) [37,38]. In agricultural areas, the direction is to limit agricultural activities within a minimum radius of 100 meters from the river border, clean drainage, build embankments, implement the concept of Soil and Water Conservation, apply agroforestry patterns, and build retention ponds or infiltration wells [39].…”
Section: Flood Mitigation Strategymentioning
confidence: 99%
“…To benefit from innovations and skills available in sectors other than government, authorities should work in partnership with business, academia, and multisector stakeholder groups. Per the study of Kurniawan et al (2021), it is vital to raise the level of youth participation in order to create a more complete disaster management program that meets regional needs. Kurniawan et al (2021) found that the amount of youth participation in flood-affected areas was higher than in unaffected areas, which was a clear difference.…”
Section: Synergy and Strategic Governancementioning
confidence: 99%
“…Per the study of Kurniawan et al (2021), it is vital to raise the level of youth participation in order to create a more complete disaster management program that meets regional needs. Kurniawan et al (2021) found that the amount of youth participation in flood-affected areas was higher than in unaffected areas, which was a clear difference. Governments should also encourage the digital transformation of public services and the use of big data applications in the provision of public services for disaster management, and they should have a concrete strategy, master plan, or governance framework in place to accomplish these goals.…”
Section: Synergy and Strategic Governancementioning
confidence: 99%
“…Compared to the other countries, Indonesia encounters floods frequently [7] [8]. In reality, the floods occur almost in every year [9] [7] and it also has the affects to 12 million people in Indonesia [10]. Special for the country, the average of the floods, which spread all over it, within about 2010 untill 2019 was 747 events in a year [11].…”
Section: Introductionmentioning
confidence: 99%